The Effect of The Use of Guided Inquiry-Based E-LKPD on Cognitive Learning Results and Students' Learning Motivation in Vibration and Wave Materials - Novalino, Alif Ajibuana; Savitri, Erna Noor (Journal of Environmental and Science Education, 2021)
The learning method using inquiry-based e-LKPD is expected to affect students' cognitive learning outcomes and the learning motivation. The research method used was a nonequivalent control group design. The research sample was taken by using the cluster random sampling technique. The results of the analysis of significant improvement in cognitive learning outcomes using N-gain showed that the experimental class was 0.40. The control class was 0.32 with the same moderate criteria. Learning outcomes related to students' motivation have also increased, which is known from the table analysis of learning outcomes for each indicator between the control and experimental classes. It can be seen that the control and experimental classes at the beginning of learning have equally low learning motivation, as evidenced by the results of the average proportion of motivation learners learning indicator by 43% in the control class and 45% in the experimental class. While the results of the final learning motivation questionnaire in the control and experimental classes both experienced an increase, but for the control class, it was still in the low category by 48% and for the experimental class experienced a significant increase of 78% with the high category.